Paradox of Islamic Secularism: Review of the Book Islamic Secularism: A Critique on Muslim Intellectuals - Majid Behestani; Mohammadreza Amirzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Historically, after the movement of constitutionalism (Mashrouteh), secularism got engaged with Iran, but it was notattended as a problematic concern for the Iranian intellectuals. When Islamic Republic of Iran was established, everything changed and it turned into the focal point. So, many questions regarding theocracy, secularism, humanism, happiness of mankind, and political Islam started to occupy the minds of many individuals. Of these concerns, some intellectuals tried to conceptualize Islamic Secularism." Mansour Mirahmadi wrote "Islamic Secularism: A Critique on Muslim Intellectuals" trying to show incapability and incompleteness of their design and its inconsistency with logic of Islam theories and practices. Reviewing the book structurally and qualitatively, we mentioned its formal and conceptual problems.